On Nudging's Supposed Threat to Rational Decision-Making. Issue 4 (29th July 2019) - Houk, Timothy
Abstract: Nudging is a tool of libertarian paternalism . It involves making use of certain psychological tendencies in order to help people make better decisions without restricting their freedom. However, some have argued that nudging is objectionable because it interferes with, or undermines, the rational decision-making of the nudged agents. Opinions differ on why this is objectionable, but the underlying concerns appear to begin with nudging's threat to rational decision-making. Those who discuss this issue do not make it clear to what this threat to rationality amounts. In this paper I evaluate what effect nudging has on our decision-making and I argue that it does not typically interfere with our rationality in a problematic way. Perhaps nudging is objectionable for other reasons, but we should not argue that nudging is objectionable based on concerns about rational decision-making.